A Two Stage Data Hiding Scheme with High Capacity Based on Interpolation and Difference Expansion. (2016) - Govind, P.V. Sabeen; Sajila, M.K.; Varghese, Bindiya M.
Abstract: A data hiding technique embeds secret information into a cover image. Cover image and the stego image look similar due to which the hackers fail to detect the presence of the hidden secret data. In this paper we propose a two stage data hiding technique with high embedding capacity. First stage is the creation of a cover image from the original input image using image interpolation, followed by the calculation of the difference between original and interpolated pixel values which is then utilized for data embedding. In the second stage, a difference expansion technique is used in the stego image to increase the payload capacity. Experimental results demonstrate that the proposed method gives better results in terms of embedding capacity and comparable results in terms of visual quality.